Pengaruh Ketersediaan Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Pada Konsumen Marketplace Tokopedia Di Kota Kalianda - Ismawati, Yeni Okta (CV. ITTC INDONESIA, 2024)
Online markets or marketplaces have become one of the main trends in electronic commerce. Tokopedia, as a marketplace platform leading in Indonesia offers various products to consumers with various marketing strategies, including product availability, pricing, and promotion. This research aims to determine the influence of product availability and price and Promotion of Purchasing Decisions either partially or partially Simultaneous, the form of this research is quantitative research. Test the instrument used in this research are validity tests and reliability tests. Technique The analysis used is multiple linear regression, correlation coefficient multiple, coefficient of determination adjusted R2, and hypothesis testing which includes the t test and f test. Collection method data with questionnaires (questionnaires) distributed to Marketplace users Tokopedia in Kalianda City. Sampling in this research used the method purposive sampling.